Correlation between plasma proBNP, echocardiographic and clinical parameters in patientswith type 2 diabetes mellitus - Irina Arkad'evna Bondar'; Daria Vladimirovna Grazhdankina; S V Ivanov; Tatiana Viktorovna Panteleeva (Сахарный диабет, 2013)
Aims. To assess plasma level of N-terminal precursor for brain natriuretic peptide (proBNP) in patients with type 2 diabetes mellitus (T2DM) and arterial hypertension without overt heart failure ? and further estimation of its correlation with data from echocardiog- raphy and clinical parameters (severity of ischemic heart disease (IHD), age, sex, duration of T2DM and hypertension experience, characteristics of glucose and lipid metabolism, renal function. Materials and methods. We examined 94 patients with T2DM and arterial hypertension (aged 40?65 years), determining character- istics of glucose and lipid metabolism and renal function. We also performed six minute walk test, ECG, echocardiography and blood tests for N-terminal proBNP (NT-proBNP) in all study subjects. Acquired data was compared to the group of 30 healthy controls. Results. We observed an increase in plasma NT-proBNP in patients with IHD, history of left venctricular (LV) myocardial infarction or clinical signs of heart failure (II NYHA class and higher). Results from patients with T2DM and arterial hypertension but without IHD did not significantly differ from control group. Plasma NT-proBNP levels correlated with left ventricular ejection fraction, left ventricular EDD and ESD, but not with LV diastolic function parameters. Duration of T2DM and arterial hypertension, HbA1c levels,27Сахар ный диабет КардиологияСахарный диабет. 2013;(1):27?32BMI, lipid and uric acid metabolism parameters had no influence on plasma NT-proBNP in diabetic patients. Conclusion. According to our study, NT-proBNP was elevated in T2DM patients with IHD (and a history of LV myocardial infarc- tion in particular) or clinical evidence for heart failure beyond II NYHA class, thus indicating unfavorable prognosis for this group of patients and need for correction of therapy with subsequent re-evaluation of plasma NT-proBNP.